Evaluation of Guava Leaf Extract Hair Tonic (Psidium Guajava L.) on Cosmetology Education Students at Medan State - Sipayung, Frenika; Sitompul, Astrid (Journal of English Language and Education, 2025)
This study aims to evaluate the formulation and consumer acceptance of a hair tonic made from guava leaf extract (Psidium guajava L.) as a natural alternative for reducing hair loss among university students. Hair loss is a common issue influenced by factors such as stress, nutritional imbalance, and prolonged use of chemical-based hair products, which may irritate the scalp and weaken hair roots. A preliminary survey conducted among 100 female students at Universitas Negeri Medan revealed that 87% experienced hair loss, and 68% preferred natural-based products, indicating the need for safer and more sustainable hair care solutions. Guava leaves contain bioactive compounds including flavonoids, tannins, and vitamins, which are known to strengthen hair roots and maintain scalp health. This research employed a quantitative descriptive method carried out at the Beauty Education Laboratory of Universitas Negeri Medan in August–September 2025. The guava leaf extract was obtained using the maceration method with 96% ethanol and formulated into a 2% hair tonic. A hedonic test was conducted with 72 panelists to assess six sensory indicators: color, aroma, texture, sensation during application, after-use aroma, and overall comfort. The findings showed that the formulation had a pH of 6.4, a viscosity of 45 cP, and caused no irritation, indicating good safety. All sensory indicators received average scores above 4.00, with acceptance levels exceeding 85%, categorized as highly liked. The product’s brownish color originated from natural tannins, its aroma from the fresh scent of guava leaf extract, and its light non-sticky texture from the combination of ethanol and propylene glycol. The cool sensation during application was attributed to ethanol, while flavonoids contributed antioxidant benefits that protect hair cells from damage. In conclusion, the guava leaf extract hair tonic demonstrates strong consumer acceptance, safe physicochemical characteristics, and promising potential as an innovative natural hair care product. These findings support further development and application of herbal-based cosmetic products aligned with sustainable beauty trends.